General and social anxiety in the BTBR T+ tf/J mouse strain - Pobbe, Roger L.H.; Defensor, Erwin B.; Pearson, Brandon L.; Bolivar, Valerie J.; Blanchard, D. Caroline; Blanchard, Robert J. (Behavioural brain research, 2011)
▶ BTBR showed enhanced anxiety in the EPM and MDTB. ▶ BTBR showed reduced anxiety in the zero-maze. ▶ BTBR showed enhanced defensiveness or anxiety-like response to another mouse. ▶ Diazepam normalized the social preference of BTBR mice. BTBR T+ tf/J (BTBR) is an inbred mouse strain that shows behavioral traits with analogies to the three diagnostic symptoms of autism spectrum disorder (ASD); deficits in social interaction, impaired communication, and repetitive behaviors with restricted interests. Previous findings reveal that when compared to C57BL/6J (B6) and other inbred strains, BTBR exhibit normal to low anxiety-like traits in paradigms designed to assess anxiety-related behaviors. The current study assessed the generality of these anxiety findings. In experiment 1, B6 and BTBR mice were tested in the elevated plus maze (EPM), mouse defense test battery (MDTB) and elevated zero-maze. BTBR mice exhibited an anxiogenic profile in the EPM, with a reduction in open arm time and an increase in risk assessment behaviors, as compared to B6. In the MDTB, BTBR showed enhanced vocalization to the predator, and significantly less locomotor activity than B6 in the pre-threat situation, but significantly more locomotion than B6 following exposure to a predator threat, suggesting enhanced defensiveness to the predator. In the zero-maze, BTBR mice showed a significantly higher number of entries and time spent in the open segments of the apparatus, when compared to B6. In experiment 2, a three-chambered social preference test was used to evaluate effects of the systemic administration of an anxiolytic compound, diazepam, on B6 and BTBR social approach. Diazepam consistently increased time in the compartment containing the social stimulus, for both B6 and BTBR mice. However, in the vehicle treated groups, B6 mice spent significantly more time while BTBR mice spent significantly less time in the social stimulus compartment; after diazepam administration both B6 and BTBR strains significantly preferred the social stimulus chamber. These results suggest that while the anxiety responses of BTBR mice to novel situations (EPM and zero-maze) are inconsistent, BTBR mice appear to be more defensive to animate threat stimuli (predator or another mouse). Reduction of anxiety by diazepam normalized the social preference of BTBR for a mouse stimulus in the three-chambered test.